Model Pembelajaran Bahasa Arab Berbasis Gamifikasi untuk Siwa Kelas XI MQNH Ulya Putri Nurul Hakim - parihin Parihin (Lembaga Penelitian dan Pengabdian Masyarakat Institut Agama Islam Nurul Hakim, 2024)
The aim of this research is to find out the concept of Arabic language learning by utilizing gamification-based learning methods for students in class XI Mqnh Ulya Putri Nurul Hakim Kediri, West Lombok. The type of research used in this research uses qualitative research. This research was conducted on Class XI students Mqnh Ulya Putri Nurul Hakim Kediri West Lombok. The data sources in this research are the Head of the Madrasah, the Class XI Arabic teacher, the students of Class The results of this research are that the Gamification-Based Learning Concept for Class XI Mqnh Ulya Putri Nurul Hakim Students reflects an innovative approach in Arabic language education. This method integrates game elements, such as points, levels, and competition, into the learning process to increase student motivation and engagement. The research results show that this approach has significant potential in improving Arabic language understanding and student learning outcomes. However, research also identifies several obstacles, including motivational distortions, unequal access to technology, and challenges in developing appropriate learning content. Therefore, this research highlights the importance of carefully designing and implementing gamification, with a focus on clear learning objectives and adequate support for students. Overall, this abstract emphasizes that the use of gamification-based learning methods has the potential to enrich Arabic language teaching at the secondary school level, but needs to be managed wisely to achieve optimal results